Plant chemical biology: are we meeting the promise? - Hicks, Glenn R.; Raikhel, Natasha V. (Frontiers in Plant Science, 2014)
As an early adopter of plant chemical genetics to the study of endomembrane trafficking, we have observed the growth of small molecule approaches. Within the field, we often describe the strengths of the approach in a broad, generic manner, such as the ability to address redundancy and lethality. But, we are now in a much better position to evaluate the demonstrated value of the approach based on examples. In this perspective, we offer an assessment of chemical genetics in plants and where its applications may be of particular utility from the perspective of the cell biologist. Beyond this, we suggest areas to be addressed to provide broader access and enhance the effectiveness of small molecule approaches in plant biology.